Analisis Pendidikan Karakter Berbasis Nilai Kearifan Local Cipta Gelar Sukabumi Dalam Mengembangkan Kecerdasan Ekologis - Ramadhan, Gilang Mas; Resmi, Citra (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2019)
This study aims to determine the dynamics of the implementation of the School Literacy Movement in the State Elementary School in Muntilan sub-district which includes 1) Teacher literacy awareness, 2) Student reading behavior and 3) Implementation of School Literacy Movement. This research is a descriptive qualitative research. The data sources of this study were 5 principals, 5 teachers, 20 students using data collection techniques through interviews, observation and documentation. The validity of the data is obtained by using source triangulation and technique triangulation. The data obtained were analyzed interactively consisting of data collection, data reduction, data presentation, drawing conclusions and verification. The data obtained is then described and analyzed. The results showed that 1) Teacher literacy awareness was not maximized so GLS implementation was not implemented 2) Majority student reading behavior was included in the Traditional Intruction category (reading related to academic material), so student literacy culture was not yet formed 3) The new GLS implementation was applied to the elementary minority Land in the district of Muntilan. The inhibiting factors that cause this condition occur are 1) The teacher does not have enthusiasm / motivation as a reader so updates to information literacy have not been maximized 2) Students lack a figure reader from the family so that low interest in reading 3) Students are addicted to devices 4) Socialization of GLS has not been deep and not accompanied by training and assistance. While the supporting factor for the implementation of GLS is the adiwiyata school program conducted in the majority of elementary schools where the program is carried out in line with the objectives of GLS, but has not yet been utilized by the school.